The Impact of Perceived Product Quality, Perceived Value, and Personality on Consumer Dissatisfaction and Complaint Behavior Types in E-commerce - Tanjung, Puti Kemala; Sumarwan, Ujang; Krisnatuti, Diah (Riviera Publishing, 2025)
The rise of e-commerce in Indonesia has significantly altered consumer behavior, particularly in post-purchase experiences. Despite increased convenience, online transactions often result in dissatisfaction due to service failures or product mismatches, prompting varying complaint behaviors. This study investigates the impact of Perceived Product Quality, Perceived Value, and Personality on dissatisfaction levels in e-commerce, and explores how complaint type (Voicer, Irate, Passive) moderates these relationships. A cross-sectional survey was conducted with 218 e-commerce consumers who had made purchases and submitted complaints, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Multi-Group Analysis (MGA). Findings show that Perceived Value emerged as the most significant and consistent predictor of dissatisfaction across all complaint types, while Perceived Product Quality and Personality showed no significant direct effect; however, Irates exhibited higher sensitivity to product quality failures. Complaint type moderated the strength of relationships, highlighting behavioral differences in consumer responses. In conclusion, consumer dissatisfaction in e-commerce is driven primarily by perceived value rather than product quality, and complaint behavior types influence how dissatisfaction is expressed but not necessarily how it is formed. The research implies that e-commerce businesses should enhance post-purchase services such as delivery, customer support, and refund systems, while tailoring complaint resolution strategies based on consumer types to reduce dissatisfaction and improve retention.